Low lymphocyte to high-density lipoprotein ratio predicts mortality in sepsis patients - Liu, Wanjun; Tao, Qian; Xiao, Jun; Du, Yijun; Pan, Tianrong; Wang, Yue; Zhong, Xing (Frontiers in Immunology, 2023)
Background: The lymphocyte-to-high-density lipoprotein (HDL) ratio (LHR) is associated with both inflammation and immunity, and may have the potential to predict the prognosis of sepsis. Our study aimed to evaluate the relationship between LHR and sepsis-related mortality. Methods: We collected data from the Medical Information Mart for Intensive Care IV (MIMIC-IV, version 2.2) database by targeting patients who met the Sepsis-3 criteria and recorded the absolute values of lymphocytes and HDL after admission. We then used restricted cubic splines based on logistic regression to simulate the relationship between the LHR and 90-day mortality. Subsequently, the hazardous threshold was derived based on the mortality curve, and further evaluations were performed using different methods and data sources for hazardous threshold. Results: We ultimately included 1027 eligible patients from the MIMIC-IV database and described the nonlinear relationship between LHR and 90-day mortality. Based on the curve, an LHR of ≤ 0.6 indicated harmful threshold, and the odds ratio for mortality was 1.74 (P=0.001). The outperforming hazard was particularly marked in patients with chronic lung disease and remained consistent after adjusting for baseline data and validating multiple data sources. Conclusions: The LHR has prognostic value in patients with sepsis, and an LHR ≤ 0.6 is a deleterious load that increases mortality.